Malnutrition cause of Secondary Osteoporosis after surgical operation of Glucagonoma - Jovanoska, Biljana; Ahmeti, Irfan; Temelkova, Snezana Markovik; Pemovska, Gordana; Dimitrovski, Cedomir; Bitoska, Iskra (Bioscientifica, 2013)
Introduction: Glucagonoma is a rare condition with annual incidence 1 in 20 million, associated with diabetes mellitus, dermatitis, deep vein trombosis and depression. Case report: A 55-year-old woman patient was hospitalized at our department because of intense discomfort of the skin lesions that were pruritic and painful, erythematous area of skin with blisters that breach after a few days, red tongue, cracks on the mouth corners. She had a constant weight loss accompanied with bloody diarrhea. Her weight was 36 kg, height 150 cm and her BMI was 16. We made 75 g OGTT and it was normal. She was misdiagnosed like contact dermatitis magnum et pedum, stomatitis protetica, erythema exsudativum multiforme, colitis. On the examination she had cheilitis angularis, atrophic glossitis, stomatitis, normochromic normocytic anemia and the Hct was 0.27, SE 70/100. She had dermatological changes – erythematous patch, blisters centrally, erodes, crusts, heals with hyperpigmentation. We made a lab test and we got that her glucagonemia was increased twice than normal. The normal values are 200 ng/l and she had 400 ng/l. We made a CT scan where a round form of a tumor was noticed in the pancreas with dimensions 5 cm width and 8 cm length. After that, she underwent a surgical operation and the surgeon made a distal splenopancreatectomy to remove the tumor. The tumor immunohistochemistry was positive of glucagon, synaptophysin and chromogranin-A. After the operation, she suffered from malnutrition and she came again at our department to check herself for osteoporosis. We made a DXA scan and we saw that she had a generalized secondary osteoporosis caused due to malnutrition after operation (T score=−4.0 on the spin, T score=−3.8 on the right hip and T score=−3.6 on the left hip). Conclusion: Long-term misdiagnosed glucagonoma explain appearance of other co-morbidites such as osteoporosis and anemia.